1982
DOI: 10.1083/jcb.95.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Topography of reaction center subunits in the membrane of the photosynthetic bacterium, rhodopseudomonas sphaeroides.

Abstract: The localization of the reaction center polypeptides (L, M, and H) in the membranes of both the wild-type, strain 2.4.1, and the carotenoidless mutant, R-26, of Rhodopseudomonas sphaeroides was determined by using affinity-purified antibodies specific for these proteins.Binding of the antibodies to reaction center subunits in spheroplasts was visualized in the electron microscope by immunoferritin labeling. The H and M subunits were labeled at both the cytoplasmic and the periplasmic surfaces of the membrane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…Both the cofactors and the L-and M-subunits exhibit an approximate twofold symmetry about a line joining the donor and the Fe. It was gratifying to us that the main features of the structure corroborated our previous findings, i.e., the L-and M-subunits have each five transmembrane helices, and the H-subunit has one (157) with most of it exposed on the cytoplasmic side (152). The cofactors are all associated with the Land M-subunits (117), the primary donor is a bacteriochlorophyll dimer (51), Q A is associated with the M-subunit (102), and the Fe is approximately equidistant from Q A and Q B (18) [for additional details, see (55)].…”
Section: Fehersupporting
confidence: 72%
See 2 more Smart Citations
“…Both the cofactors and the L-and M-subunits exhibit an approximate twofold symmetry about a line joining the donor and the Fe. It was gratifying to us that the main features of the structure corroborated our previous findings, i.e., the L-and M-subunits have each five transmembrane helices, and the H-subunit has one (157) with most of it exposed on the cytoplasmic side (152). The cofactors are all associated with the Land M-subunits (117), the primary donor is a bacteriochlorophyll dimer (51), Q A is associated with the M-subunit (102), and the Fe is approximately equidistant from Q A and Q B (18) [for additional details, see (55)].…”
Section: Fehersupporting
confidence: 72%
“…Most anti-H preparations labeled the cytoplasmic side, and only one out of six labeled the periplasmic side. From this we concluded that H is asymmetrically oriented with respect to the membrane, most of it being on the cytoplasmic side (152).…”
Section: Further Characterization Of the Rcmentioning
confidence: 96%
See 1 more Smart Citation
“…The M subunit has been shown to span the cytoplasmic membrane by several labeling techniques (31,32). The sequence obtained from the gene was examined for potential membrane-spanning regions by the method of Kyte and Doolittle (33).…”
Section: Discussionmentioning
confidence: 99%
“…The RC is an oligomeric integral membrane protein complex in which each subunit may span the membrane (1,18,39), and it has been proposed that L and M each contain five membrane-spanning regions (42,43). Therefore, the arrangment of the subunits in the membrane is, undoubtedly, quite complex.…”
Section: Discussionmentioning
confidence: 99%